2008
DOI: 10.1007/s11512-007-0063-8
|View full text |Cite
|
Sign up to set email alerts
|

Sharp estimates for maximal operators associated to the wave equation

Abstract: We give almost sharp conditions under which the maximal operator associated with the wave equation with initial data in Sobolev space H^s(R^n) is bounded from H^s(R^n) to L^q(R^n).Comment: 7 pages, 1 figur

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…In higher dimensions n ≥ 2 it was proven by Vega [21] that (1.2) holds for q ≥ 2(n+2) n and n+1 q + 1 r ≤ n 2 . When n = 2 Rogers [15] showed it for 2 ≤ r < ∞, q > 16 5 and 3 q + 1 r < 1, and later the excluded endline 3 q + 1 r = 1 was obtained by Lee-Rogers-Vargas [11]. When n ≥ 3, Lee-Rogers-Vargas [11] improved the previous known result to r ≥ 2, q > 2(n+3) n+1 and n+1 q + 1 r = n 2 .…”
Section: Intoductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In higher dimensions n ≥ 2 it was proven by Vega [21] that (1.2) holds for q ≥ 2(n+2) n and n+1 q + 1 r ≤ n 2 . When n = 2 Rogers [15] showed it for 2 ≤ r < ∞, q > 16 5 and 3 q + 1 r < 1, and later the excluded endline 3 q + 1 r = 1 was obtained by Lee-Rogers-Vargas [11]. When n ≥ 3, Lee-Rogers-Vargas [11] improved the previous known result to r ≥ 2, q > 2(n+3) n+1 and n+1 q + 1 r = n 2 .…”
Section: Intoductionmentioning
confidence: 73%
“…For a case of the wave operator it is known that (1.2) holds for (r, q) pairs such 2 ≤ r ≤ q, q = ∞ and 1 r + n−1 2q ≤ n−1 4 (see [8,9,13,18]). Particularly, when r = ∞, Rogers-Villarroya [16] showed that (1.2) with regularity s > n( 12 − 1 q ) − 1 r is valid for q ≥ 2(n+1) n−1 . For the fractional Schrödinger operator the known range of (r, q) for which the estimates hold is that 2 ≤ r ≤ q, q = ∞ and n 2q + 1 r ≤ n 4 (see [1,2,4,12,20]).…”
Section: Intoductionmentioning
confidence: 99%
“…Another application is a sharp maximal function estimate. In [9], Rogers and Villarroya proved the following sharp maximal estimate for the wave operator in R d :…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In dimension one, Carleson 1 proved that the pointwise convergence () holds if s14, which is proved to be sharp by Dahlberg and Kenig 2 through constructing the counterexample. In higher dimensions, one can see previous studies 3–14 for details.…”
Section: Introductionmentioning
confidence: 90%